Preschoolers’ executive function: effect of the duration of preschool attendance and quality of teacher-child interactions - Gavrilova, Margarita; Karimova, Aleksandra; Solopova, Oksana; Veraksa, Aleksander; Yakushina, Anastasia (Frontiers in Education, 2024)
The aim of this study was to determine the role of duration of preschool attendance and the quality of teacher-child interactions in the executive functions development of preschoolers. The study involved 947 children (51% girls) age 4–7 years (M = 70.3 months; SD = 4.3). The number of children attending kindergarten for less than 1 year was 144; 268 children (28.3%) had attended for 1 to 2 years; and 535 children (56.5%) had attended for more than 2 years. The results showed that the children who attended a group with a high quality of teacher-child interaction for one or more years had better results on verbal work memory, and cognitive and physical inhibitory control than those who attended the same group over a shorter period.